Tensiomyographic Responses to Warm-Up Protocols in Collegiate Male Soccer Athletes - Michael J. Redd; Tristan M. Starling-Smith; Chad H. Herring; Matt S. Stock; Adam J. Wells; Jeffrey R. Stout; David H. Fukuda (Journal of Functional Morphology and Kinesiology, 2021)
The mechanical properties of knee flexors and extensors in 15 collegiate male soccer players following different warm-up protocols [small-sided games (SSG), dynamic (DYN), and plyometric (PLY)] were evaluated. Tensiomyography (TMG) was used to assess contraction time (Tc), delay time (Td) and maximal displacement (Dm) of the rectus femoris (RF) and biceps femoris (BF) of both legs before and after each warm-up, while countermovement jump height variables, 20 m sprint, t-test and sit-and-reach were measured following the warm-ups. TMG was analyzed using a three-way [condition × time × leg] ANOVA, while performance variables were analyzed with a repeated measures ANOVA. Main effects of time were observed for BF-Tc (p = 0.035), RF-Td (p < 0.001), and BF-Td, (p = 0.008), and a main effect of condition was seen for RF-Tc (p = 0.038). Moreover, participants’ 20 m sprint improved following SSG (p = 0.021) compared to DYN and PLY. Sit-and-reach was greater following PLY (p = 0.021). No significant interactions were noted for the measured TMG variables. Warm-up-specific improvements were demonstrated in sprint speed and flexibility following SSG and PLY, respectively. The present study revealed changes in certain TMG measures following the warm-ups that suggest enhanced response of lower leg muscles regardless of specific activities used.